2011
DOI: 10.1016/j.brainresbull.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexually diergic hypothalamic–pituitary–adrenal (HPA) responses to single-dose nicotine, continuous nicotine infusion, and nicotine withdrawal by mecamylamine in rats

Abstract: Hypothalamic-pituitary-adrenal (HPA) responses to single-dose nicotine (NIC) are sexually diergic: Female rats have higher adrenocorticotropic hormone (ACTH) and corticosterone (CORT) responses than do males. In the present study we determined HPA responses in male and female rats following single doses of NIC, a single-dose of NIC immediately following continuous NIC for two weeks, and NIC withdrawal by single-dose mecamylamine (MEC) following continuous NIC infusion for two weeks. Blood sampling occurred bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…This is consistent with findings from other laboratories showing that female rodents display an increase in anxiety-like behavior and plasma corticosterone levels during nicotine withdrawal. [31][32][33][34] The present study also revealed a different pattern of changes in CRF receptor gene expression during nicotine exposure and withdrawal. Specifically, both CRF-R1 and CRF-R2 gene expression was decreased during nicotine exposure in intact females.…”
Section: Discussionsupporting
confidence: 57%
“…This is consistent with findings from other laboratories showing that female rodents display an increase in anxiety-like behavior and plasma corticosterone levels during nicotine withdrawal. [31][32][33][34] The present study also revealed a different pattern of changes in CRF receptor gene expression during nicotine exposure and withdrawal. Specifically, both CRF-R1 and CRF-R2 gene expression was decreased during nicotine exposure in intact females.…”
Section: Discussionsupporting
confidence: 57%
“…Female rats showed greater adrenocorticotropic hormone levels during nicotine withdrawal. Corticosterone increased only in females in response to nicotine after continuous nicotine exposure, and corticosterone responses were increased in females after the precipitation of withdrawal (Gentile et al, 2011). In other studies, female rats exhibited greater symptoms of nicotine withdrawal, including an exaggerated stress response, compared with males (Torres and O'Dell, 2015).…”
Section: Sex Differences In Drug Abusementioning
confidence: 69%
“…For example, plasma corticosterone levels are increased to a greater extent in female versus male rats following repeated injections (Gentile et al, 2011; Moidel et al, 2006; Rhodes et al, 2001; 2004; Skwara et al, 2012) and continuous delivery (Faraday et al, 2005) of nicotine. In an in vitro perfusion system, the presence of nicotine increased CRF and ACTH levels to a greater extent in hypothalamic tissue that was collected from female versus male rats (Mcklveen et al, 2010; Moidel et al, 2006).…”
Section: Pre-clinical Research On the Long-term Effects Of Nicotinmentioning
confidence: 99%